International business, sustainability and corporate social responsibility - Gonzalez-Perez, Maria-Alejandra; Leonard, Liam (Advances in sustainability and environmental justice,, 2013)
This is the first in a two volume study of Corporate Social Responsibility and corporate behaviour from around the world, taking in viewpoints from five continents and over ten countries. These case studies present a detailed analysis of best practice in the corporate world in the areas of social ethics and community engagement.